2007
DOI: 10.1007/s00216-007-1424-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling methods for the determination of phenolic compounds in foods and dietary supplements

Abstract: Profiling methods are needed that separate and detect all the phenolic compounds in a single extract of a food material. These methods must be comprehensive, rapid, and rich in spectral information. Fourteen methods that meet, or have the potential to meet, these criteria have been selected from the recent literature for review. In general, the methods employ a single aqueous methanol extraction, separation on a reversed-phase C column, and detection by UV/vis spectroscopy and mass spectrometry. The variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 49 publications
0
50
0
11
Order By: Relevance
“…Based on the slope of the linear relationship between Q and t 1/2 , A can be calculated to be 0.00116 cm 2 and 0.00297 cm 2 for the GCE and CoHCF/Au/SBA-15/GCE, respectively ( Figure 8B). The results indicated that the electrode effective surface area was increased obviously after modification of the GCE with CoHCF/ Au/SBA-15/GCE, which could enhance the total adsorption capacity of catechol, leading to the increase of current response of catechol, decreasing the limit of detection ( Figure 9).…”
Section: Chronocoulometry Studies Of the Gce And Modified Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the slope of the linear relationship between Q and t 1/2 , A can be calculated to be 0.00116 cm 2 and 0.00297 cm 2 for the GCE and CoHCF/Au/SBA-15/GCE, respectively ( Figure 8B). The results indicated that the electrode effective surface area was increased obviously after modification of the GCE with CoHCF/ Au/SBA-15/GCE, which could enhance the total adsorption capacity of catechol, leading to the increase of current response of catechol, decreasing the limit of detection ( Figure 9).…”
Section: Chronocoulometry Studies Of the Gce And Modified Electrodesmentioning
confidence: 99%
“…Recent decades, considerable efforts have been invested in the determination of phenolic compounds in environmental, industrial, agricultural, and food fields [1,2]. Phenolic compounds are released into environment by a large number of industries, such as coal mining, oil refinery, paint, polymer and pharmaceutical preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…); agrotóxicos (e.g., DDT); e outras espécies, como CN -, benzeno, clorofórmio, etc. Além disso, esta lista inclui uma classe muito importante de poluentes, que tem sido alvo de pesquisas acadêmicas, [10][11][12] que são os compostos fenólicos.…”
Section: Química Verde (Qv): Definição E Princípiosunclassified
“…Assim, novos procedimentos foram (CN) 10 ] 10-(coloração verde) concentrado desenvolvidos, os quais empregam principalmente microextração em fase líquida (MEFL), microextração em fase sólida (MEFS), análise em fluxo, extração por ponto nuvem (EPN) e, mais recentemente, sistema aquoso bifásico (SAB). MEFL e MEFS são usualmente aplicadas ao preparo de amostras para posterior determinação via CG ou CLAE, com diferentes sistemas de detecção.…”
Section: Conclusãounclassified